Wireless IP and Building the Mobile Internet - Dixit, Sudhir (Artech House, 2011)
Written by experts in academia and industry, this manual takes a comprehensive look at the convergence of wireless and Internet technologies that are giving rise to the mobile wireless Internet. This resource offers practitioners an overview of all the elements required to understand and develop future IP (Internet Protocol) based wireless multimedia communications and services.